التسامح الفكري بين القرآن الكريم والعهد الجديد الحوار والجدال انموذجاً (دراسة مقارنة) - Ansam Z. Muhey ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
In this article we tried to present an idea of tolerance in the divine religions between the Qur’an and the New Testament, by shedding light on the issue of intellectual tolerance (dialogue and controversy model ), which is one of the important issues, which the Qur’an’s calls to focus it to the call to God Almighty. And the method are among the means of peaceful intellectual persuasion, and I have invested them. With God Almighty, by drawing the correct approach that the nation can respond to the many suspicions that are attached to Islam, and to contribute to correcting the concepts of (intolerance,coercion,violence,exclusion),as well as intellectual tolerance in dialogue and controversy in the enrichment of the idea of ​​Muslims discussing their relations with Muslims, from cooperation, to live in isolation from others.